Patterns of variation in the interplay of language ability and general reading comprehension ability in L2 reading. (July 2019) - Löwenadler, John
This study aims to investigate patterns of variation in the interplay of L2 language ability and general reading comprehension skills in L2 reading, by comparing item-level effects of test-takers' results on L1 and L2 reading comprehension tests. The material comes from more than 500, 000 people tested on L1 (Swedish) and L2 (English) in the Swedish Scholastic Assessment Test (2010–16). The statistical analysis found no significant correlations between degree of L2 language focus and text length or sentence length, nor could any significant differences be found with regard to the language focus in main point, inference or retrieval items. However, a statistically significant difference was found between the rational deletion gap test and the two sections based on content questions on long and short texts, in the sense that the former to a greater degree measures language ability. Moreover, even though the gap test consists of semantic deletion only, specifically aiming to test higher-order skills, the effect size by different measures was consistently large (Cohen's d around 0.8). Finally, an additional, more exploratory, qualitative study supported the connection between the distribution of the operationalized language focus value and an item's relative focus on higher- or lower-level reading skills. Furthermore, it gave some indication that strongly language-focused content question items may be characterized by intra-sentential complexity relating to syntactic parsing and semantic-proposition encoding more than to unfamiliar vocabulary. However, with regard to the results of the qualitative section, more research is clearly needed before it is possible to draw any general conclusions.